Leading people at different stages of personal development: an actionable framework for practitioners balancing emotional support and growth for a conscious future - Luedi, Markus M.; Goldsworthy, Susan (Frontiers in Psychology, 2025)
Leadership is no longer just about directing tasks or achieving short-term goals. It is about navigating complexity, fostering growth, and addressing the human dimension of work in an era of constant change. Today’s leaders are expected to balance emotional support with strategic challenges, a dynamic process that empowers teams to thrive while fostering personal development. However, effectively guiding individuals at different stages of personal growth remains challenging. We present a conceptual synthesis that integrates insights from developmental psychology, integral theory, philosophy, neuroscience, and contemporary leadership concepts (e.g., authentic, adaptive, transformational, and servant leadership) to explore the transformative concept of “secure base leadership.” The originality of this paper lies not in surveying a wide range of thinkers, but in integrating the core strands into a coherent framework for leadership across stages of personal development.